The effectiveness of dual-task exercises in individuals with chronic obstructive pulmonary disease: a study protocol for a randomized controlled trial - Begüm Ünlü; Aysel Yıldız Özer; İpek Özmen; Mine Gülden Polat (Trials)
Abstract Background Central nervous system dysfunction is an extrapulmonary complication of chronic obstructive pulmonary disease (COPD), and brain function, particularly frontal lobe function, has been shown to deteriorate. It has also been reported that the time taken to complete a functional test involving a cognitive task is prolonged in patients with COPD. The aim of this study is to evaluate the effect of dual-task performance on motor and cognitive function in COPD and to determine the effect of dual-task exercises delivered in a pulmonary rehabilitation program on cardiopulmonary and musculoskeletal parameters. Methods COPD patients who are admitted to pulmonary rehabilitation, meet the inclusion criteria, and volunteer to participate will be randomly divided into the pulmonary rehabilitation group (control group) and dual-task exercise group. The Dual Task Exercise Group will continue the established rehabilitation programs. During the walking and balance exercises in the program, they will also do cognitive exercises, which are different from those in the pulmonary rehabilitation control group. The COPD Assessment Questionnaire will be applied, and dyspnea assessment will be done with the Modified Medical Research Council Dyspnea Scale. Mini-Mental State Examination and Frontal Assessment Battery will be used to assess cognitive status. Mini-BESTest: Balance Evaluation Systems Test will be used to assess balance. Functional balance and mobility assessment will be performed with the Timed Up and Go Test and the 10-m Walk Test. The tests will be applied twice, as a single task (normal walking) and a dual task (walking and cognitive task). The 6-min walk test will be used to assess functional capacity. Quality of life will be assessed using the St. George Respiratory Questionnaire. Results of pulmonary function tests performed at routine check-ups will be obtained. Assessments will be repeated at the end of the 8-week exercise program. Discussion Extrapulmonary clinical problems may affect the treatment process in COPD. Studies examining the effect of cognitive dysfunction evaluated dual-task performance in COPD and compared it with healthy controls. Despite the differences in the results, it emphasized that the effects of adding dual-task training to pulmonary rehabilitation should be investigated. Our study may contribute to the literature at this point. Trial registration ClinicalTrials.gov ID: NCT05930158 (Date: 14.06.2023).